The Bumiputera Policy: Views from the Chinese Business Community - Chin Yee Whah (Kajian Malaysia, 2003)
This paper analyses the views of the Chinese business community toward the Bumiputera Policy. This study is based on primary data drawn from in-depth interviews conducted in 1996, 1997, 1999 and 2003 with 62 Chinese entrepreneurs in the small and medium enterprises (SMEs), in Peninsular Malaysia. The study revealed some old and new views of the policy